2007
DOI: 10.1364/ao.46.004294
|View full text |Cite
|
Sign up to set email alerts
|

Interest of broadband optical monitoring for thin-film filter manufacturing

Abstract: Broadband optical monitoring for thin-film filter manufacturing is more and more developed thanks to better performances of spectrometers with array detectors. We compare this optical monitoring with turning point monitoring and quartz monitoring of different designs. The sensitivity to thickness errors and to refractive index errors is evaluated. We show that real time determination of deposited thickness is a valuable criterion. We also present our experimental setup of transmittance and reflectance broadban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…This monitoring system has been first tested through the manufacturing of beamsplitters and edge filters. As expected, the monitoring capabilities are improved compared to those of the previous system [8].…”
Section: Description Of the Optical Monitoring Systemsupporting
confidence: 67%
“…This monitoring system has been first tested through the manufacturing of beamsplitters and edge filters. As expected, the monitoring capabilities are improved compared to those of the previous system [8].…”
Section: Description Of the Optical Monitoring Systemsupporting
confidence: 67%
“…A set of three hall sensors has been mounted close to the rotating substrate holder to generate trigger signals to initi ate spectrometer measurements when the substrate holder is in the relevant position. It has frequently been shown that broadband optical monitoring is extremely useful for highperformance coating deposition, when (environmentally) stable and reproducible optical film constants are guaranteed by the choice of a suitable deposition technique such as ion beam sputtering (IBS), magnetron sputtering (MS), ion plating, or (plasma) ionassisted electron beam evaporation ((P)IAD) [22,23]. Particularly, the suitability of the OptiMon system for monitoring PIAD processes using a Leybold APSpro plasma source [24] has frequently been demonstrated for PIAD processes at IOF.…”
Section: Experimental Setup and Measurement Of The Optical Sample Promentioning
confidence: 99%
“…The component is then much more robust, which justifies the generalization of monochromatic optical control to all complex optical filters with narrow band (as presented here). On the contrary for the fabrication of broadband filters, a "Broadband" control is particularly well suited [60,61].…”
Section: Introductionmentioning
confidence: 99%